Изменения климата и динамика берегов Украины - Горячкин, Ю.Н.; Иванов, В.А. (Видавничий дім "Академперіодика" НАН України, 2008)
The influence of climate changes on the coast dynamics of the Western Crimea is considered. It is shown that the natural reasons of the modern abrasion of coasts are an increase of the Black Sea level and changes of the wind-wave mode, which results in an increase of the wind speed and the recurrence of storms from the most wind-dangerous directions.